2017
DOI: 10.1080/15548627.2016.1256522
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors (GIST): Facing cell death between autophagy and apoptosis

Abstract: Autophagy and apoptosis are 2 fundamental biological mechanisms that may cooperate or be antagonistic, although both are involved in deciding the fate of cells in physiological or pathological conditions. These 2 mechanisms coexist simultaneously in cells and share common upstream signals and stimuli. Autophagy and apoptosis play pivotal roles in cancer development. Autophagy plays a key function in maintaining tumor cell survival by providing energy during unfavorable metabolic conditions through its recyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 102 publications
0
39
0
Order By: Relevance
“…Changes in autophagy and apoptosis play an essential role in the development of cancer, and autophagy and apoptosis often interact in a complex manner . Autophagy can inhibit or promote cell apoptosis due to different cell types, environments and stimuli .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in autophagy and apoptosis play an essential role in the development of cancer, and autophagy and apoptosis often interact in a complex manner . Autophagy can inhibit or promote cell apoptosis due to different cell types, environments and stimuli .…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of autophagy in CaOx kidney stones remains largely unknown. Moreover, it has been recently documented that nanomaterials could induce cell death through the crosstalk between autophagy and apoptosis, the two main mechanisms of programmed cell death . Thus, this study aims to investigate the occurrence of autophagy induced by CaOx nanocrystals in a human renal proximal tubular epithelial cell line HK‐2.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature reviews and our clinical experience, we found that patients with GIST were generally well-tolerated with imatinib (19). DeMatteo and colleagues conducted a randomized phase III, double-blind, placebo-controlled, multicenter trial about patients with GIST treated with imatinib (20), showing that grade I and II adverse events were common and mostly involved gastrointestinal effects, headache, rash, edema, fatigue, and myalgias/arthralgias.…”
Section: Introductionmentioning
confidence: 99%